Constitutional theories of international organisations: beyond the west - Peters, Anne (Chinese journal of international law, 2021)
The Joint Statement by the Foreign Ministers of China and Russia on Certain Aspects of Global Governance in Modern Conditions of 23 March 2021 calls for “the establishment of a fairer, more democratic and rational multipolar world order.” The paper inquires how constitutional theories of international organisations have in the past and present sought to contribute to world order. It identifies three waves of such theory since the 1960s. Looking in more detail at the ongoing third wave, it identifies and seeks to pull out further a constitutional model which upscales the proto-democratic practices in international organisations by strengthening forums for participation and contestation, which rectifies to the north-south imbalance inter alia rooted in the colonial heritage by involving more actors from the global south, and which tackles the global social question upfront.